Metafora Ganda Bagi Yesus Kristus Dalam Wahyu 5:5-6: Memahami Perjanjian Baru Dalam Menggunakan Perjanjian Lama - Moses Wibowo; Jonidius Illu; Oren Siregar (Sekolah Tinggi Teologi Torsina Surakarta, 2021)
The Old and New Testaments are the primary sources of understanding the identity and work of Jesus Christ. There was a consensus from commentators that the combination of the Lion and the Lamb as a double metaphor for Jesus Christ in Revelation 5:5-6 is one of the complex texts and was also crucial to being able to understand the entire book of Revelation. Restrospectively this section has presented multi-interpretation so that it also affects the theological and practical understanding of interpreters. This article will approach the metaphorical combination in Revelation 5:5-6 biblically primarily by dividing the interpretation steps in accordance with the NT use of the OT. This point in the book of Revelation is related to the identity and work of Jesus Christ in order to carry out the divine dual mission: judgment and salvation, to establish the kingdom of God on earth through love and not through violence.